Education law reform: is this an opportunity to ensure inclusion in education in Colombia? - Caballero Pérez, Adriana (DIXI, 2026)
Colombia is undergoing a major legal reform process in various areas, including education. In 2023, the national government submitted the draft Statutory Law on Education for debate. Is this an opportunity to guarantee the right to non-discrimination and equality for people with disabilities in the educational context? The short answer is yes. With the aim of contributing to the political discussion on education in the country, this article analyzes the Colombian State’s obligation to guarantee inclusive education for persons with disabilities in compliance with international human rights law and Article 24 of the Convention on the Rights of Persons with Disabilities (CRPD). Based on this analysis, the opportunities and challenges facing Colombian legislators have been identified. It is concluded that there are at least three critical points for social and democratic discussion prior to the adoption of a new education law: equal opportunities for all, adequate investment of public resources, and the effectiveness of the measures adopted for inclusion.